2017
DOI: 10.1016/j.ebiom.2017.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Opening a Can of Worms: Leprosy Reactions and Complicit Soil-Transmitted Helminths

Abstract: Background> 94% of new annual leprosy cases are diagnosed in populations co-endemic for soil-transmitted helminths (STH). STH can profoundly dysregulate host immune responses towards Th2 bias, which can be restored over time after deworming. We hypothesize that STH co-infection is associated with leprosy reaction (denoted as simply “reaction” herein) occurrence within a co-endemic population.MethodsA cohort study was performed on a cohort of Nepalese leprosy patients across treatment and diagnostic classificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Furthermore, it is worthy to note that leprosy is a complicated disease with different immunological processes playing a role in disease progression, which in turn are affected by factors such as genetics[ 27 ], co-infections[ 28 ] as well as food-shortage[ 29 ]. The combination of these factors with the long incubation time that elapses before leprosy becomes clinically manifest, makes predicting which M .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is worthy to note that leprosy is a complicated disease with different immunological processes playing a role in disease progression, which in turn are affected by factors such as genetics[ 27 ], co-infections[ 28 ] as well as food-shortage[ 29 ]. The combination of these factors with the long incubation time that elapses before leprosy becomes clinically manifest, makes predicting which M .…”
Section: Discussionmentioning
confidence: 99%
“…For example, certain helminth-derived proteins can bias the host immune response towards an anti-inflammatory Th2 response, which may facilitate M . leprae growth or progression to MB leprosy[ 28 ]. Furthermore, a period of food shortage can reduce cell mediated immunity of individuals incubating M .…”
Section: Discussionmentioning
confidence: 99%
“…Granting M. leprae transmission is not completely understood, risk factors for development of leprosy have been identified including close contact with untreated, multibacillary patients(3), human susceptibility genes(4, 5), infection with soil transmitted helminths(6), as well as food shortage(7).…”
Section: Introductionmentioning
confidence: 99%
“…13 This study also showed a higher odds of STH in multibacillary (MB) versus paucibacillary leprosy cases, an association which Diniz et al 14 also demonstrated in Brazil. On the other hand, Hagge et al 15 found a lower risk of reactions in STH-positive participants.…”
Section: Introductionmentioning
confidence: 95%